Beyond El Barrio : Everyday Life in Latina/o America. - Pérez, Gina M., 1968- (NYU Press, 2010)
Freighted with meaning, "el barrio" is both place and metaphor for Latino populations in the United States. Though it has symbolized both marginalization and robust and empowered communities, the construct of el barrio has often reproduced static understandings of Latino life; they fail to account for recent demographic shifts in urban centers such as New York, Chicago, Miami, and Los Angeles, and in areas outside of these historic communities. Beyond El Barrio features new scholarship that critically interrogates how Latinos are portrayed in media, public policy and popular culture, as well a.